Evaluation of a New Tubular Finger Oxygen-Enriched Oil Inside-Coated Dressing Device in Pediatric Patients Undergoing Distal Hypospadias Repair: A Prospective Randomized Clinical Trial Part II - Esposito, Ciro; Coppola, Vincenzo; Del Conte, Fulvia; Cerulo, Mariapina; Esposito, Giovanni; Crocetto, Felice; Castagnetti, Marco; Calignano, Antonio; Escolino, Maria (Frontiers in Pediatrics, 2021)
Background: This study was the second part of a prospective randomized clinical trial and aimed to evaluate the use of a tubular finger oxygen‑enriched oil inside-coated dressing device and its effect on the post-operative outcome of children undergoing distal hypospadias repair. Methods: A prospective single-blinded randomized clinical trial was carried out between September 2019 and September 2020. We included all patients with distal hypospadias, who received Snodgrass urethroplasty and preputioplasty. The patients were randomized in two groups according to the type of dressing: tubular finger oxygen-enriched oil inside-coated device (G1) and elastic net bandage with application of oxygen-enriched oil-based gel (G2). The patients were evaluated at 7, 14, 21, 30, and 60 post-operative day (POD). Results: Sixty-four patients (median age 14 months) were included in the study and randomized in two groups, each of 32 patients. Post-operative preputial edema rate was significantly lower in G1 (3/32, 9.3%) compared with G2 (10/32, 31.2%) (p=0.001). The median duration of preputial edema was significantly shorter in G1 compared with G2 (6 vs 10.5 days) (p=0.001). Penile diameter measurements at 4th, 7th, 14th POD proved that entity and duration of post-operative swelling were objectively decreased using the new dressing. The wound healing was significantly faster in G1 compared with G2 (14.2 vs 18.5 days) (p=0.001). The post-operative complications rate was significantly lower in G1 (0%) compared with G2 (3/32, 9.3%) (p=0.001). Foreskin dehiscence occurred in two G2 patients (6.2%) whereas breakdown of urethroplasty and preputioplasty occurred in one G2 patient (3.1%) due to scratching injuries. The dressing management was subjectively assessed by nurses to be easier in G1 patients compared with G2 ones (median score 1.2 vs 3.5) (p=0.001). The median treatment costs were significantly lower in G1 compared with G2 (55 vs 87 eur) (p=0.001). No adverse skin reactions occurred. Conclusions: Post-operative dressing using tubular finger oxygen-enriched oil inside-coated device was highly effective, easy to manage, cheaper and associated with a lower rate of foreskin and urethral complications compared with the standard dressing method in pediatric patients undergoing distal hypospadias repair. It was also clinically safe without allergy or intolerance to the product.